2000
DOI: 10.2337/diabetes.49.7.1269
|View full text |Cite
|
Sign up to set email alerts
|

A new mitochondrial DNA mutation at 14577 T/C is probably a major pathogenic mutation for maternally inherited type 2 diabetes.

Abstract: From a family of 16 diabetic patients with typical maternal inheritance, we investigated a 69-year-old woman with type 2 diabetes. The proband showed no major deletions in the mitochondrial DNA (mtDNA). Direct sequencing revealed 7 missense and 5 ribosomal RNA homoplasmic nucleotide substitutions when compared with the Cambridge Sequence and its recent revision. When compared with the control cybrid cells, the proband cybrid cells showed 6 nucleotide substitutions. Among these, 14577 T/C, which turned out to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…This patient had type 2 DM diagnosed before the age of 40 and presented neurosensorial deafness and cardiomyopathy. The T14577C mutation in the NADH-dehydrogenase 6 (ND6) gene was fi rst identifi ed in 1.2% of a sample of Japanese type 2 diabetic patients, not being observed in any subject of the control group (17). We found this mutation in a patient with "classical" type 2 DM and also in a patient within the MIDD group.…”
Section: Discussionmentioning
confidence: 92%
“…This patient had type 2 DM diagnosed before the age of 40 and presented neurosensorial deafness and cardiomyopathy. The T14577C mutation in the NADH-dehydrogenase 6 (ND6) gene was fi rst identifi ed in 1.2% of a sample of Japanese type 2 diabetic patients, not being observed in any subject of the control group (17). We found this mutation in a patient with "classical" type 2 DM and also in a patient within the MIDD group.…”
Section: Discussionmentioning
confidence: 92%
“…Mitochondrial single nucleotide polymorphisms (mtSNPs) C1310T, A1382C, G1438A, A1202G, A3252G, A3256T, A3264C, A3271C, T3290C, C3303T, G3316A, T3394C, A5178C, A8296G, A8344G, A10398G, G11778A, A12026G, C12258A, T14577C, T14709C, T16519C, A14693G and T16189C etc have been reported to be associated with T2DM (Tawata et al 2000;Mohlke et al 2005;Salles et al 2007;Liou et al 2007;Bhat et al 2007a, b). Most of these variants are rare and many are associated with additional traits such as deafness, neurological symptoms, or myopathy.…”
Section: Methodsmentioning
confidence: 99%
“…Tawata et al reported that mtDNA mutations at nucleotides 1310, 12026, and 14577 are associated with type 2 diabetes, 22,23 and several SNPs in the NADH dehydrogenase subunit genes have been reported in patients with Parkinson's disease. 24 There have been a few studies addressing the associations between mitochdrial polymorphism and diseases, [25][26][27][28][29] but further studies are needed to clarify the role of the mitochodrial genotype in common diseases.…”
Section: Discussionmentioning
confidence: 99%